Macrophage activity at the site of tumor ablation can promote murine urothelial cancer via transforming growth factor-β1 - Kimura, Yasushi; Fujimori, Masashi; Rajagopalan, Neeraj Raghuraman; Poudel, Krish; Kim, Kwanghee; Nagar, Karan; Vroomen, Laurien GPH.; Reis, Henning; Al-Ahmadie, Hikmat; Coleman, Jonathan A.; Srimathveeravalli, Govindarajan (Frontiers in Immunology, 2023)
Cell death and injury at the site of tumor ablation attracts macrophages. We sought to understand the status and activity of these cells while focusing on transforming growth factor-β1 (TGF-β1), a potent immunosuppressive and tumorigenic cytokine. Patients with urothelial cancer who underwent ablation using electrocautery or laser demonstrated increased infiltration and numbers of CD8+ T cells, along with FoxP3+ regulatory T cells, CD68+ macrophages and elevated levels of TGF-β1 in recurrent tumors. Similar findings were reproduced in a mouse model of urothelial cancer (MB49) by partial tumor ablation with irreversible electroporation (IRE). Stimulation of bone marrow derived macrophages with MB49 cell debris produced using IRE elicited strong M2 polarization, with exuberant secretion of TGF-β1. The motility, phenotypic markers and cytokine secretion by macrophages could be muted by treatment with Pirfenidone (PFD), a clinically approved drug targeting TGF-β1 signaling. MB49 cancer cells exposed to TGF-β1 exhibited increased migration, invasiveness and upregulation of epithelial-mesenchymal transition markers α-Smooth Muscle Actin and Vimentin. Such changes in MB49 cells were reduced by treatment with PFD even during stimulation with TGF-β1. IRE alone yielded better local tumor control when compared with control or PFD alone, while also reducing the overall number of lung metastases. Adjuvant PFD treatment did not provide additional benefit under in vivo conditions.